Religion and Culture Syncretism in the Klenik Tradition in the Javanese Community of Binjai City - Alwiyah, Sasi; Sahrul, Sahrul (JUSPI (Jurnal Sejarah Peradaban Islam), 2024)
It has become a classic thing that culture cannot be separated from the lives of people who follow their respective religions. For us Muslims, not all cultures are in line with religious teachings. One of them is the occult tradition which is considered shirk by several Islamic figures. However, in reality, this tradition is still widely practiced by the Javanese people in Sumber Mulyo Rejo Village, Binjai City, the majority of whom are Muslim. This illustrates the syncretism between religion and culture in the occult tradition. This research aims to examine the form of syncretization of the occult tradition. In this case, the researcher uses a type of qualitative research with a phenomenological approach. The data collection tools used were observation, documentation and interviews. The data sources in this research are interviews with village elders and people who practice this tradition. From the research conducted, the results can be concluded that the syncretization process in Sumber Mulyo Rejo Village begins with occult traditions that are difficult to eradicate as well as beliefs that have been passed down from generation to generation regarding the community's understanding of these traditions. So, it can be said that the value of syncretization in this tradition lies in the procedures and forms of belief of the Javanese people in Sumber Mulyo Rejo Village towards this occult tradition, for example, they still believe in the activities of throwing salt and burning sulfur around the house to protect against the supernatural.